Assessment of the Real Estate Market Value in the European Market by Artificial Neural Networks Application - Jasmina Ćetković; Slobodan Lakić; Marijana Lazarevska; Miloš Žarković; Saša Vujošević; Jelena Cvijović; Mladen Gogić (Complexity)
Using an artificial neural network, it is possible with the precision of the input data to show the dependence of the property price from variable inputs. It is meant to make a forecast that can be used for different purposes (accounting, sales, etc.), but also for the feasibility of building objects, as the sales price forecast is calculated. The aim of the research was to construct a prognostic model of the real estate market value in the EU countries depending on the impact of macroeconomic indicators. The available input data demonstrates that macroeconomic variables influence determination of real estate prices. The authors sought to obtain correct output data which show prices forecast in the real estate markets of the observed countries.